Pre-stressed concrete proceedings of the conference arranged by the Joint Committee on Materials and Their Testing of Technical Institutions and Societies in Great Britain and held under the auspices of the Institution of Civil Engineers, February, 1949. (Institution of Civil Engineers, 1949)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of a conference held in 1949, with an introductory paper by FG Thomas.